Inovasi Penilaian Qawaid Nahwiyah Dalam Buku Teks Bahasa Arab Kelas XII Berbasis Penilaian HOTS - Aulia, Nimas; Baroroh, R Umi (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
The aim of this study is to analyze HOTS-based test instruments for assessing Qawaid nahwiyah and innovation in class XII Arabic textbooks published by the Ministry of Religion in 2020. This research uses qualitative research methods; the approach used adopts library research techniques. Data analysis methods used include content analysis and descriptive analysis. The main source of data comes from an Arabic book published by the Ministry of Religion of the Republic of Indonesia in 2020 for class XII. In addition, secondary data sources in research involve journals, books, and other relevant data. The results of this research show that there are 9 questions on the Qawaid Nahwiyah instrument test, 1 HOTS question at the C4 level, and 8 other questions at the MOTS level. The innovations made to the HOTS-based Qawaid Nahwiyah test instrument produced 10 new questions, which included 8 C4-level questions, 1 C5-level question item, and 1 C6-level question item. In this research, there are several new HOTS-based instruments, including: pronouncing words or phrases in sentences; comparing sentence structures; determining correct and incorrect sentences; explaining types of words; identifying and correcting sentence errors; as well as providing comments and assessing. different rules in a sentence.